Development of a methodology to model the dynamic properties of UAVS and high-order control systems - Vasilyev, G. S.; Kuzichkin, O. R.; Kurilov, I. A.; Surzhik, D. I. (Revista de la Universidad del Zulia, 2020)
When modeling the dynamic properties of an unmanned aerial vehicle (UAV) and an automatic control system (ACS), it is often necessary to take into account factors such as the lack of rigidity of the aircraft structure, the influence of control and destabilizing factors, which leads to an increase in the order of the model under study. The known numerical and analytical methods do not allow us to obtain general solutions for the variable parameters of the high-order system under study, and at the same time provide the required amount of error and computational costs. A method is developed to model the dynamic properties of UAVs and high-order control systems based on the spectral method, the linear approximation by parts of the input control actions and the spectrum of the system’s output signal. An example of using the technique to model the dynamic properties of different orders ACS UAVs (from 1 to 10) with different types of inertia is considered. Based on the analysis of errors in the calculation of the transition process, the effectiveness of the method for analyzing high-order systems is shown based on the required computational costs.